2006
DOI: 10.1002/jms.981
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric characterization of lipid‐modified peptides for the analysis of acylated proteins

Abstract: The analysis of acylated proteins by mass spectrometry (MS) has largely been overshadowed in proteomics by the analysis of glycosylated and phosphorylated proteins; however, lipid modifications on proteins are proving to be of increasing importance in biomedical research. In order to identify the marker ions and/or neutral loss fragments that are produced upon collision-induced dissociation, providing a means to identify the common lipid modifications on proteins, peptides containing an N-terminally myristoyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 45 publications
5
35
0
Order By: Relevance
“…Differences in acyl chain length between lipid substrates were documented by 28-Da shifts in a series of corresponding b and y ions. Comparison of fragmentation patterns of differently modified peptides is especially important because thioester modifications often do not produce a marker or neutral loss ions; therefore backbone fragmentation appears to be the primary way of peptide decomposition (23). In conclusion, we directly demonstrated that LRAT forms transient thioester bonds during enzymatic activity, providing proof for previous hypotheses.…”
Section: Expression and Purification Of Lrat-gst Fusionsupporting
confidence: 68%
“…Differences in acyl chain length between lipid substrates were documented by 28-Da shifts in a series of corresponding b and y ions. Comparison of fragmentation patterns of differently modified peptides is especially important because thioester modifications often do not produce a marker or neutral loss ions; therefore backbone fragmentation appears to be the primary way of peptide decomposition (23). In conclusion, we directly demonstrated that LRAT forms transient thioester bonds during enzymatic activity, providing proof for previous hypotheses.…”
Section: Expression and Purification Of Lrat-gst Fusionsupporting
confidence: 68%
“…This is because there is an inverse correlation between the prevalence of the neutral loss and the charge state of the precursor ion that was observed in the product ion analysis of the sulfinamide modified-test peptides (Fig. 2) as well as in a previous study (52). If the modification has a low proton affinity and the molecular ion is in a low charge state, the probability that the modification fragments as a neutral fragment increases.…”
Section: Global Proteome Analysis For Discovery Of Hno-induced Modifisupporting
confidence: 51%
“…Recently, also direct mass spectrometric techniques have been applied for the analysis of farnesylated peptides using MALDI-and ESI-mass spectrometry (Hoffman and Kast, 2006). While precursor ion scanning (reporter ion C 15 H 25 , m = 205 Da) is favourable for ESI-MS, for MALDI-MS neutral loss scanning (loss of C 15 H 24 , Dm = 204.3 Da) should be preferred but also peptide fragments can yield these ions, e.g.…”
Section: Protein Prenylationmentioning
confidence: 99%
“…In a recent report (Hoffman and Kast, 2006) also ESI-NLS has been used for palmitoylation of cysteines using the loss of C 16 H 30 OS (Dm = 272 Da). However, no marker ions were obtained which could have been used for PIS.…”
Section: Protein Acylationmentioning
confidence: 99%